Relative Abundance, Diversity and Threats of Avian Fauna at Dhanmondi Lake in Dhaka, Bangladesh (Jagannath University Journal of Life and Earth Sciences, 2024)
A study was conducted on the relative abundance, diversity, and threats of avifauna in Dhanmondi Lake, Dhaka, Bangladesh from March to December 2021. Data was collected by following the line transect sampling method and direct field observations, where four days were spent every month in the study area. A total of 34 species of birds were observed, belonging to 9 orders and 20 families. Out of 34 species of birds, 94% were residents and 6% were migrants; of them, 55% were non-passerines and 45% were passerines. The relative abundance of avifauna was also estimated as 29% of species being very common, 15% being fairly common, 27% being common, and 29% being few. The highest number of individuals was observed in December (209 individuals), followed by 199 individuals in April, 189 individuals in March, 187 individuals in October, 178 in November, 177 in August, and 170 in June. The Shannon-Weiner index was estimated to be at its maximum (H′ = 2.98) in March-21, and its minimum value was obtained (H′ = 2.62) in June-21. Similarly, the value of Simpson’s index of diversity was obtained to be maximum (D = 0.09) in June-21 and minimum (D = 0.06) in December-21. Human activities such as large gatherings, random assemblies, festivals, dumping of waste, throwing of papers, polythene, and plastics here and there, and finally, noises from the different vehicles, were identified as major threats to avian species.Jagannath University Journal of Life and Earth Sciences, 9(1): 95–109, 2023 (June)